Indigenous knowledge systems and indicators of rain: Evidence from Rwenzori Region, Western Uganda - Nkuba, Michael Robert; Chanda, Raban; Mmopelwa, Gagoitseope; Mangheni, Margaret Najjingo; Lesolle, David; Kato, Edward (American Meteorological Society, 2020)
This study investigated the abiotic and biotic environmental indicators used among pastoralists and arable farmers to predict the onset and cessation of rain as well as to make short-term and seasonal forecasts in the Rwenzori region of Western Uganda. We used a mixed-methods approach that included surveys of 907 households, focus group discussions, and key informant interviews. The results indicate that resident birds such as white-browed coucals and turacos and migrant birds such as eagles and swallows were important indicators of the onset of rains. Butterflies were an important indicator for the cessation of rains, and red ants were an indicator for the onset of rains. Among the abiotic indicators, winds, clouds, earthquakes, and cloud formation on Mount Rwenzori were important indicators. Behavior of cattle at the onset of rains was important among the pastoralists, and flowering of coffee plants was important among the arable farmers. The behavior of the biotic indicators was driven by the availability of food, water, or other necessities. An attempt to explain the phenology underlying the behavior of biotic indicators and the meteorological science underlying some of the abiotic indicators is made. Although biotic environmental indicators are rudimentary and their accuracy is influenced by external factors such as climate change, they provide climate information within the locality of the farmers. Our results suggest that the indicators used in indigenous forecasting could be incorporated in national meteorological systems in a bid to improve the accuracy of rainfall forecasts and their use among farmers and pastoralists in rural Africa.